Linguistic strategies in the construction of power relations in call-in conversations in Vuuka FM vernacular radio station - Musimbi, Catherine Musimbi; Atichi, Alati R; Mandilla, Lucy (Nairobi Journal of Humanities and Social Sciences, 2023)
This paper examines how language is used to enact power and identity as manifested n caller’s texts in Vuuka FM radio station, a vernacular radio station broadcasts in Luloogoli. This paper seeks to respond to the following objective, to determine the power relations manifested in the call in conversations of Vuuka FM radio station. This study was carried out in Vihiga County in Western Kenya among the Lulogooli speakers. Fairclough’s (2001) Critical Discourse Analysis approach , whose main tenet is a critical analysis of caller texts in terms of the manifestations of power relations, was used for the analysis of caller conversations. A qualitative approach to data collection was adopted where a total of thirty call-in programmes were purposively sampled for transcription and analysis according to the thematic areas that were selected. The paper established that there was manifestation of power relations in the conversations of callers that creates two divergent groupings, ‘them ’the subjugated group, versus ‘us’ the dominant group. Furthermore, callers through their discourses manifested distinct ideologies depending on the roles assigned to the different groupings in society. The findings of this paper would be of help to linguists and other language scholars in that it would contribute to the development of research on the use of indigenous languages.